Effectiveness of Pyridostigmine and Pyridoxine in Vinca AlkaloidInduced Cranial Neuropathy – A Case Series - Gupta, Aparajita; Roy, Shuvendu; Paul, Prateep (Journal of Nepal Paediatric Society, 2022)
The neurotoxicity of the vinca alkaloids in the form of peripheral neuropathy is well known, however, cranial neuropathy is not widely recognized especially in children. We describe here in three children with malignancies who developed vinca alkaloid induced cranial nerve palsies during treatment which resolved on institution of pyridoxine and pyridostigmine. Vinca-alkaloid-induced cranial nerve palsies represent a potentially dangerous but reversible condition.